The Use of Integral Citation in English Students’ Final Project Reports - Nugraha, Danny; Khorina, Mulyati; Agoes, Farida; Sulyaningsih, Iis (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2023)
This paper is concerned with integral citation employed by English students of Politeknik Negeri Bandung in their Final Project Reports (FPR). Thus, the aims of this study were to investigate the most integral citation type used by the students in their FPR. In conducting the study, 18 FPR focusing on analysis produced in 2022 were collected as data source. Applying qualitative method and text analysis, the results reveal several things. First, the students favor integral citation than non-integral citation. Second, verb controlling appears more than naming. In verb controlling citation, lexical verb state is commonly used compared with other lexical verbs. Whereas in naming, the phrase according to + the cited authors is the mostly used. this study has implication in improving the students’ academic skills, especially in doing citation.